Hubungan Kehamilan Lewat Waktu dan Preeklampsia Berat (PEB) dengan Kejadian Asfiksia Neonatorum - Pera Mandasari (STIKES Citra Delima Bangka Belitung, 2020)
Asphyxia neonatorum is a condition where the baby cannot breathe spontaneously and regularly (Prawirohardjo, 2010). The purpose of this study was to determine the relationship of pregnancy over time and severe preeclampsia with the incidence of asphyxia neonatorum in Prabumulih City Hospital. The research method is analytic, using the Cross Sectional approach. The study population was all mothers who gave birth in the midwifery room of Prabumulih City Hospital. The research sampling method with a random sampling method is 321 people. The results of the study are based on bivariate analysis it is known that of the 26 respondents who experienced a pregnancy beyond time there were 19 respondents (5.9%) who gave birth to a baby with asphyxia, while of 295 respondents who did not experience a pregnancy beyond the time there were 38 respondents (11.9%) who delivered babies with asphyxia, of the 55 respondents who experienced severe preeclampsia there were 40 respondents (12.5%) who gave birth to babies with asphyxia, while of the 266 respondents who did not experience severe preeclampsia there were 17 respondents (5.3%) who gave birth to a baby with asphyxia. Conclusions there is a significant relationship between pregnancy over time with the incidence of asphyxia with a P value of 0,000 ≤ α 0.05 and there is a significant relationship between severe preeclampsia with the incidence of asphyxia with a P value of 0,000 ≤ 0.05.